Clinical features and treatment of maturity onset diabetes of the young (MODY) - Gardner DS,Tai ES (Diabetes, Metabolic Syndrome and Obesity, 2012)
Daphne SL Gardner1, E Shyong Tai21Department of Endocrinology, Singapore General Hospital, 2Department of Endocrinology, National University Hospital, SingaporeAbstract: Maturity onset diabetes of the young (MODY) is a heterogeneous group of disorders that result in ß-cell dysfunction. It is rare, accounting for just 1%–2% of all diabetes. It is often misdiagnosed as type 1 or type 2 diabetes, as it is often difficult to distinguish MODY from these two forms. However, diagnosis allows appropriate individualized care, depending on the genetic etiology, and allows prognostication in family members. In this review, we discuss features of the common causes of MODY, as well as the treatment and diagnosis of MODY.Keywords: type 1 diabetes, type 2 diabetes, HNF1A, HNF4A, HNF1B, GCK